Role of CT scan in evaluation and management of intestinal obstruction - Baid, Gaurav; Dawan, Manohar Lal; Parmar, Ashok (International Surgery Journal, 2017)
Background: Intestinal obstruction is one of the most common diseases in abdominal surgery. It can slowly lead to changes in intestinal structure and function, and in extreme cases it can be life-threatening. CT allows imaging of the abdominal contents outside the lumen, because of this advantage, the nature and site of the obstruction, especially extraluminal or intramural process, can be established. Methods: Prospective Hospital Based study. From January 2016 to November 2016 (11 months). 50 Patients presenting to Department of Surgery, whether in OPD or Emergency, with complaints suggestive of intestinal obstruction with in study duration eligible as per inclusion criteria will be included in the study. Results: In present study Majority (52.0%) of study population belonged to 41-60 years age group. The most common symptom was pain abdomen (94%). Majority (66%) patients showed multiple air fluid level on X-ray. In CT imaging, maximum 36% presented with dilated bowel loops. 86% were diagnosed as sub-acute intestinal obstruction, in USG. In present study, 60% patients were treated by surgery. Majority of patients (86.67%) CT findings matched with perop/ intraoperative findings. Accurate CT findings were helpful in guiding patient management. In our study, CT had the sensitivity of 86.67%, Specificity75%. Conclusions: Management decisions in intestinal obstruction remain notoriously difficult, relying on a combination of clinical and imaging factors to help stratify patients into conservative or surgical treatment.